From Words to Worlds: Metaphor Translation of Zootopia from the Perspective of Functional Equivalence Theory - Huilin Ji (Journal of Linguistics and Communication Studies, 2025)
This study aims to analyze the types of metaphor in the animated film Zootopia and explore effective translation strategies to promote cross-cultural communication. Employing text analysis and case study methods, this research examines subtitle translation strategies under the framework of functional equivalence theory. The finding reveals that the application of vocabulary equivalence and cultural equivalence can effectively steer the translation of metaphors in Zootopia, offering strategic guidance to translators. These strategies enhance the quality of metaphor translation in animated films, fostering greater audience understanding and acceptance of the film, and facilitating cross-cultural communication through animated cinema. This study also provides a useful reference for related research and translation practice.